Effect of Sb and N resonant states on the band structure and carrier effective masses of GaAs1-x-yNxSby alloys and GaAs1-x-yNxSby/GaAs quantum wells calculated using k·p Hamiltonian. (June 2017) - Mal, Indranil; Samajdar, D.P.; Das, T.D.
Abstract: GaAsNSb is a promising candidate for use in GaAs-based optoelectronic devices in the 1.33–1.55 μm wavelength region. We have calculated the band structure of dilute nitride-antimonide GaAs1--x--y Nx Sby alloys, lattice matched to GaAs, using Band anticrossing (BAC) and Valence Band Anticrossing (VBAC) model in conjugation withk·p Hamiltonian method. This mathematical model in the form of a 16 band Hamiltonian matrix is used to examine the shift of different bands as a function of Sb concentration for both bulk and quantum well structures for GaAsNSb/GaAs. The band parameters such as energy gap, spin-orbit splitting energy, carrier effective masses, band offsets, and strain generated due to the growth of GaAsNSb/GaAs heterostructures as a function of Sb and N concentrations are calculated and compared with the recent experimental data. The substitution of As atoms due to the incorporation of N and Sb impurity atoms causes a significant band gap reduction of ∼330 meV for GaAs0.931 Sb0.05 N0.019 alloys. The enhancement of spin-orbit splitting energy causes a crossover between Eg and Δ s o for Sb and N concentration of 27 and 10 at % respectively. Suitable tuning of the band offset values with Sb and N concentrations makes GaAsNSb/GaAs alloy system an efficient alternative for band gap engineering and fabricating photonic device structures. Highlights: Band structure of GaAsNSb alloys and GaAsNSb/GaAs QWs calculated using 16 band k dot p Hamiltonian. Carrier effective masses, band offsets and strain calculated as function of Sb and N concentration. Band gap of GaSbBiN calculated using k dot p method, VBAC and CBAC models. Larger values of calculated Conduction band offset can help in carrier confinement. Quantum confinement potential and energy levels calculated for 10 nm wide GaAsNSb/GaAs QWs.